Looking at Our Schools through a Positive Psychological Lens - Maree, Tracey (Trinity College (Dublin, Ireland). School of Education, 2020)
Looking at our Schools through a Positive Psychological Lens Tracey Maree The University of Dublin. Trinity College Dublin. In general, our pupil’s emotional well-being is a very prominent factor in Ireland’s educational frameworks. However, regardless of best-intentioned policies and practice, the current phenomenal rise in depression, mental health disorders, self-harm and suicide amongst our pupils and young adults is simply quite alarming. At present, there is an epidemic of anxiety and depression, and as teachers, school leaders and managers, we are witnessing it occurring younger and younger. In order to help address this surge in psychological difficulties, this study examines how pupils respond to strengths-based teaching strategies that are based on positive psychology principles. It then investigates if the implementation of a such an innovative pedagogical approach could help teachers and school leaders and managers realise some of the aims and objectives as outlined in DES’s Looking at our Schools: A Quality Framework for Primary Schools (2016). In order to conduct this action research, a positive psychology strengths-based programme was developed and implemented over the course of one month to a combined class of Senior Infant and First-Class pupil participants within an Irish primary school. The strategy used for data collection and research included an induction programme, which introduced pupils to character strengths via the guise of child friendly character-building thought affirmations. Role play, explicitly associated with the character-building thoughts, was also used to facilitate gradual skills acquisition in positive human interactions and behaviour. Finally, a group interview took place to capture the pupil’s involvement in the study, their understanding of positive psychology principles, and explore their favourite and least favourite aspects of the programmes content and implementation. The findings reveal that teaching strategies based on positive psychology principles, when combined with a high-quality curriculum that supports social and emotional development and competence, can vigorously support mental health and well-being, social learning, and positive behaviour. The research study has also established that from a leadership and management perspective, some of the aims and objectives outlined in DES’s Looking at our Schools: A Quality Framework for Primary Schools (2016) can be met and realised through the implementation process of such a positive psychological pedagogical approach. This study contributes to the existing literature as it examines the results of a positive psychology programme being implemented in an Irish context. Looking at our Schools through a Positive Psychological Lens appears to offer some convincing alternative pedagogical solutions to mental health and well-being promotion.
Keywords: Education; Leadership and Management in Education